Preseason neck mobility is associated with throwing-related shoulder and elbow injury, pain and disability in college baseball pitchers - Devaney, L. L.; Denegar, C. R.; Thigpen, C.; Lepley A.; Edgar C.; DiStefano, L (Journal of Athletic Training, 2019)
Context: Shoulder and elbow injuries in baseball pitchers have been on the rise for three decades at all levels of play and result in significant pain and disability. Despite anatomical and neurophysiological relationships, neck mobility impairments have not been explored as contributors to shoulder and elbow injury in baseball pitchers. The purpose of this study was to investigate the relationship between cervical/thoracic spinal mobility and risk of shoulder and elbow pain and disability in college baseball pitchers. Methods: This was a prospective cohort study. Forty-nine healthy college baseball pitchers (19.92 ±1.48 years, 187.04 ±6.02 cm, 89.14 ± 12.08 kg) were enrolled prior to the 2018 college season. Posture, neck mobility, and glenohumeral passive range of motion were measured during preseason using the Inclinometric Kyphosis Measure, Cervical Flexion Rotation Test, Cervical Active Range of Motion (CROM®), and digital incli-nometry, respectively. Time-loss (days lost to shoulder or elbow injury) was recorded, and patient reported disability was captured bi-weekly using the Functional Arm Scale for Throwers (FAST). Pitchers were dichotomized into Injured and Uninjured groups based on time-loss (> 7 days) and cutoff scores for average FAST (> 10). Receiver Operating Characteristic curves were generated, and diagnostic accuracy values and risk ratios (RR) were calculated to assess the diagnostic utility of the physical measures. Results: Ten pitchers (20.4%) sustained a time-loss injury (> 7 days) due to shoulder or elbow injury. A dominant side Cervical Flexion Rotation Test of <39° resulted in over 9 times increased risk of time-loss injury (RR=9.38, 95%CI 1.2868.49, p=.028). Dominant side Cervical Flexion Rotation Test of <38°, Cervical Flexion Range of Motion < 64°, and mass > 86.86 kg were also associated with increased risk of patient reported pain and disability >10 on the FAST Pitcher Module ((RR=4.05, 95%CI 1.02-16.04, p=.030; RR=8.90, 95% CI 1.27-62.26, p=.014; and RR= 10.42, 95%CI 1.14-213.70, p=.008, respectively). Conclusions: College baseball pitchers with less neck mobility during preseason had increased risk of both time-loss and patient reported shoulder and elbow pain and disability during the season. Predictive value of these measures as part of a risk screening profile should be further explored.